2020
DOI: 10.3390/molecules25132956
|View full text |Cite
|
Sign up to set email alerts
|

Production of Lactic Acid from Carob, Banana and Sugarcane Lignocellulose Biomass

Abstract: Lignocellulosic biomass from agricultural residues is a promising feedstock for lactic acid (LA) production. The aim of the current study was to investigate the production of LA from different lignocellulosic biomass. The LA production from banana peduncles using strain Bacillus coagulans with yeast extract resulted in 26.6 g LA·L−1, and yield of 0.90 g LA·g−1 sugars. The sugarcane fermentation with yeast extract resulted in 46.5 g LA·L−1, and yield of 0.88 g LA·g−1 sugars. Carob showed that addition of yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Similarly, the most important LA productivity (1.12 g/l/h) reported by Costa et al [36] in their study on lactic acid production from agri-food residues as carbon sources is lower than that highlighted in the present work. The use of carob, banana, and sugarcane lignocellulose biomass for LA production was the subject of a study conducted by Azaizeh et al [37]; it revealed that LA production from these carbohydrate substrates with yeast extract were 54.8 g/l, 26.6 g/l, and 46.5 g/l, It was found that the production of LA would depend on nature and chemical composition of the carbohydrate and protein substrates in the fermentation broth and would also depend on the fermentation strain and fermentation conditions [3,7,10,38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the most important LA productivity (1.12 g/l/h) reported by Costa et al [36] in their study on lactic acid production from agri-food residues as carbon sources is lower than that highlighted in the present work. The use of carob, banana, and sugarcane lignocellulose biomass for LA production was the subject of a study conducted by Azaizeh et al [37]; it revealed that LA production from these carbohydrate substrates with yeast extract were 54.8 g/l, 26.6 g/l, and 46.5 g/l, It was found that the production of LA would depend on nature and chemical composition of the carbohydrate and protein substrates in the fermentation broth and would also depend on the fermentation strain and fermentation conditions [3,7,10,38].…”
Section: Discussionmentioning
confidence: 99%
“…This has prompted researchers to search for cheap sources of carbon for LA fermentation. For instance, LA ranging from 26.6 to 54.8 LA L −1 was produced from banana, sugarcane, and carob wastes using Bacillus coagulans strains 104 . Sreenath et al 105 .…”
Section: Strategies For Valorization Of Crop Residuesmentioning
confidence: 99%
“…For instance, LA ranging from 26.6 to 54.8 LA L −1 was produced from banana, sugarcane, and carob wastes using Bacillus coagulans strains. 104 Sreenath et al 105 demonstrated the production of LA from alfalfa fiber, soya fiber, corn cob, and wheat straw using SSF by LAB strains. Lactobacillus plantarum yielded more LA (46 g 100 g −1 fiber) with alfalfa fiber while L. delbrueckii produced more LA (44 g 100 g −1 fiber) with soya fiber than other substrates.…”
Section: Organic Acidsmentioning
confidence: 99%
“…Therefore, the initial concentration of simple mixed sugar substrates was fixed at 30 g/L, which is equivalent to the fermentable sugar expected to be achieved from 100 g dried corn stover or other lignocellulosic substrates [22]. Azaizeh, et al [48] recommended that 10% dry matter (DM) was suitable for lignocellulose biomass pretreatment and hydrolysis and DM higher than 15% may cause a technical problem due to high viscosity [49].…”
Section: L-la Production From Mixed Glucose and Xylose By Coculture Fermentationmentioning
confidence: 99%